Definição de zonas de manejo em lavouras agrícolas a partir de mapas de produtividade: estudo de caso - Barato, Márcio Adair (2014)
Based on productivity maps and data analysis it is possible for the producer to check and act over the low yielding areas, maximizing the final productivity that way. This paper intents to show the importance of the usage of precision agriculture maps on farms in order to help farmers to determine low yielding areas and act over it, improving productivity. This paper and the generated maps referred during the text were made using John Deere equipment and AMS (Agricultural Management Solutions). The studied area is a 19ha (190.000m²) total area, located at Faxinal, Paraná state. Five maps were analyzed totaling a 3 years range period of samples that were used later for interpolation. The interpolations and adjustments done were made using Apex® and CR Campeiro® software. The output of this interpolation is a single map that shows some tendencies for some areas to present low, medium and high yield. Those regions represent 5,95%, 86,25% and 7,80% respectively. This map is a base for the final analysis that will provide information to develop and increase productivity in low yielding areas.